Escola de tempo integral e ludicidade: os pontos de vista de alunos do 1º ano do ensino fundamental - Azevedo, Nair Correia Salgado (2014)
This study is related to the expansion of elementary school in Brazil from eight to nine years, and the implementation of full-time education in the city of Presidente Prudente (São Paulo). The Cidadescola Program followed the guidelines proposed by the Ministry of Education, including the recommendation to enhance the fun and games. In this scenario, the objectives of this study are to understand the Cidadescola Program under the expansion of elementary education policies and the implementation of full-time school; to investigate the points of view of children on the activities undertaken in this context, paying special attention to the theme of playfulness. This is an ethnographic study, based on participant observation and on various strategies for the field data collection. It was found that children emphasize relationships among themselves and leisure practices that promote movement. In the case of the school studied, it was also concluded that there is a risk of an opposition between the regular shift of classes and the opposite shift of these classes, as if there were two different schools in the same school unit. However, didactic and pedagogical guidelines present in specialized literature and official documents, as well as the perspective of the children themselves, point towards the need for a full-time school, therefore, integrated.